Arabinoxylan hydrolyzates as immunomodulators in lipopolysaccharide-induced RAW264.7 macrophages. Issue 7 (30th June 2016) - Mendis, Mihiri; Leclerc, Estelle; Simsek, Senay
Abstract : The immunomodulatory effects of arabinoxylan (AX) have been demonstrated before. However, these effects could be structure driven. Thus, we indicate the relationship between fine structural details and immunomodulatory properties of AX. Abstract : Inflammation is an important healthy immune response of the body during lesions and infection. However, uncontrolled excessive inflammation can be damaging to the cells. The specific objective of this research was to evaluate the effect of structural details of enzymatically derived wheat arabinoxylan hydrolyzates (AXH) on their immunomodulatory properties. Out of the 30 AXH, six AXH showed statistically significant reduction in NO production compared to the control, causing an approximately 24 to 12% reduction in NO production. Five AXH exhibited statistically significant pro-inflammatory properties in the LPS induced cells, causing an approximately 10 to 14% increase compared to the control. A negative correlation was seen between NO production and total arabinoxylan (AX) × amount of 1, 4-linked xylose with arabinose substituted at the O-3 position. Thus, AXH with higher AX and substitution at the O-3 position are favorable candidates to reduce the lipopolysaccharide induced inflammation. These results suggest that there may be a structure–function relationship for these AXH as immunomodulators.